KEPEMIMPINAN PEREMPUAN DI PERGURUAN TINGGI: MANAJERIAL ATAU AKADEMIK - Susilo Surahman; Muhammad Munadi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
Female leadership in the college field still shows a small percentage compared to men. On the other hand, there is a leadership dilemma faced by women at the top, between being managerial leaders or academic leaders. This paper aims to describe the model of female leadership in college. This research is qualitative research with a normative approach. The results showed that women who entered the realm of leadership, in general, have a feminist and transformative leadership style. Feminist leadership is a particular characteristic inherent in female leaders, while transformative leadership is a solution to women's leadership dilemmas. Transformative leadership itself prioritizes the process of change and improvement in an organization.